Using Brain-Based Interventions to Address Ninth Grade Students’ Misconceptions about Newton’s Laws: Descriptions of Secondary Teachers’ Action Research - Deborah Brown (The Advocate, 2016)
This study describes four secondary physics teachers’ action research investigations and perceptions of the action research process. Each of the action research projects used key aspects of brainbased teaching to address students’ misconceptions about physics. Foremost among these were the use of technology and collaborative work with peers; these approaches enabled students to make meaningful connections, do a learning activity, and demonstrate understanding. The projects yielded positive effects on post assessments of students’ understanding. The four teachers reported numerous benefits from doing action research, though they noted several important caveats.